2016
DOI: 10.5301/tj.5000377
|View full text |Cite
|
Sign up to set email alerts
|

Three Patients with Multiple Myeloma Developing Secondary Lymphoblastic Leukemia: Case Reports and Review of the Literature

Abstract: Multiple immune defects caused by exposure to a variety of agents can play an important role in the development of secondary lymphoblastic leukemia. Microscopic morphology and flow cytometry are important means to detect secondary malignancies in multiple myeloma. Further clinical, experimental and genetic studies of secondary malignancies in multiple myeloma will be necessary in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the reported cases, the majority of secondary malignancies in MM were acute myelocytic leukemia (AML), myelodysplastic syndrome (MDS) and solid tumors ( 4 7 ). In a previous study, the present authors reported 3 cases of MM who developed lymphoblastic leukemia after exposure to a variety of agents ( 9 ). The present study reports the case of a patient who developed secondary lymphoblastic leukemia 38 months after the initial MM diagnosis.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the reported cases, the majority of secondary malignancies in MM were acute myelocytic leukemia (AML), myelodysplastic syndrome (MDS) and solid tumors ( 4 7 ). In a previous study, the present authors reported 3 cases of MM who developed lymphoblastic leukemia after exposure to a variety of agents ( 9 ). The present study reports the case of a patient who developed secondary lymphoblastic leukemia 38 months after the initial MM diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…A very low percentage of similar blast cells were found in the bone marrow smears during maintenance therapy in all those 3 cases ( 9 ). It is not known whether the subsequent occurrence of secondary B-cell lymphoblastic leukemia represents a transformation of MM into a less differentiated B-cell malignancy, a biclonal neoplasm arising from an oncogenic event in a common B-cell precursor, or an independent oncogenic event due to the defect in immune dysregulation ( 4 , 6 9 ). However, if a low percentage of blast cells is noticed early on, flow cytometry may be introduced and provide further evidence of disease, and the patient may also have a chance for early intervention.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We report our institution's experience with eight patients diagnosed with t-B-ALL or incipient t-B-ALL in the setting of therapy for MM, including lenalidomide maintenance therapy. While therapy-related malignancies in this setting are far more commonly myeloid neoplasms [13] , recent reports of t-B-ALL in the literature reflect increasing recognition of this entity [ 10 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. t-B-ALL is rare or under-recognized, with <50 reported cases to our knowledge individually or in small series, and additional cases described within larger analyses [ 30 , 31 ] Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…large number of literatures have reported that the risk of secondary hematological tumors in tumor patients is significantly higher than that in ordinary people[3] [4][5]. In recent years, with the prolongation of the survival time in MM patients, the incidence rate of MM related second tumors was increased[6].Studies show that there is a causal relationship between the treatment of primary malignant tumors and the incidence of secondary tumors.…”
mentioning
confidence: 99%